Intestinal protozoa of animals in Macedonia - HIMONAS (Χ. Α. ΧΕΙΜΩΝΑΣ), C. Α.; ANTONIADOU-SOTIRIADOU (Κ.Σ. ΑΝΤΩΝΙΑΔΟΥ-ΣΩΤΗΡΙΑΔΟΥ), K. S.; SOTIRAKI (Σ.Τ. ΣΩΤΗΡΑΚΗ), S. T.; PAPAZACHARIADOU (Μ.Γ. ΠΑΠΑΖΑΧΑΡΙΑΔΟΥ), M. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The infection with intestinal protozoa of clinically healthy animals which was as follows:100 cattle (Bos taurus europeus aged 2-5 years), 70 buffaloes (Bubalus bubalis, 2-5 years), 273 sheep (2-5 years), 147 goats (1-5 years), 110 horses (5-25 years), 141 pigs (2 months-4 years), 8 bears (2-30 years), 103 cats (1-7 years) and 291 chickens (35 days-4 years),it was investigated in certain areas of Macedonia. Determination of the prevalence of infection was based on faecal examination. Eight species of intestinal protozoa were identified. The most prevalent protozoa per animal were: Entamoeba spp. in cattle (92%), buffaloes (100%), sheep (70.6%) and goats (56.5%); Balantidium spp. in pigs (68.8%); Buxtonella sulcata in buffaloes (100%); Blastocystis spp. in chickens (63.9%), bears (75%) and buffaloes (100%); Eimeria spp. in horses (54.5%) and buffaloes (100%) and Giardia spp. in cats (20.3%) and buffaloes (100%). The following genera are reported here for the first time in some hosts in Greece: Cryptospporidium in horses, goats and cats, Giardia in buffaloes, sheep, goats, cats and chickens, Blastocystis in horses, buffaloes, sheep, pigs, cats, bears and chickens, Entamoeba in cattle, buffaloes, sheep, goats, pigs, cats, bears and chickens, Buxtonella sulcata in cattle and buffaloes and Eimeria in buffaloes. Furthermore, this appears to be the first report of Blastocystis in horses, sheep, buffaloes and bears, Balantidium in sheep and goats, Entamoeba in buffaloes and bears and Giardia in buffaloes and chickens.